2016
DOI: 10.3310/hta20210
|View full text |Cite
|
Sign up to set email alerts
|

The Protease Inhibitor Monotherapy Versus Ongoing Triple Therapy (PIVOT) trial: a randomised controlled trial of a protease inhibitor monotherapy strategy for long-term management of human immunodeficiency virus infection

Abstract: BackgroundStandard-of-care antiretroviral therapy (ART) for human immunodeficiency virus (HIV) infection uses a combination of drugs, until now considered essential to minimise treatment failure and development of drug resistance. Protease inhibitors (PIs) are potent with a high genetic barrier to resistance and have the potential for use as monotherapy after viral load (VL) suppression achieved on combination therapy. However, longer-term resistance and toxicity risks are uncertain.ObjectiveTo compare the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 84 publications
0
17
1
Order By: Relevance
“…This, however, does not have to translate into an alteration of the FG [23]. In our study, however, a slight decrease in mil/min of GFR during treatment with DRV/COBI was observed, at week 24 and 48.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This, however, does not have to translate into an alteration of the FG [23]. In our study, however, a slight decrease in mil/min of GFR during treatment with DRV/COBI was observed, at week 24 and 48.…”
Section: Discussioncontrasting
confidence: 75%
“…Secondly, the "pure ITT" or "switch-included" endpoint may have been interpreted differently across the studies -long-term follow-up after switching off randomized medication is essential for this endpoint to be collected. Thirdly, PIVOT trial [22,23] could not be included in the main analyses of efficacy, because the data had been presented using Kaplan-Meier curves, which were not consistent with the analyses of the other trials at fixed time-points.…”
Section: Discussionmentioning
confidence: 99%
“…Histograms revealed that the cost data were right-skewed; therefore, gamma distribution was used. For QALYs, as suggested in a previous National Institute for Health Research Health Technology Assessment report, 67 decrement of QALY was originally predicted in the regression using a gamma distribution. Decrement of QALY was calculated as the difference between the maximum QALYs that could possibly be accrued within the time frame and the actual QALY gained.…”
Section: Discussionmentioning
confidence: 99%
“…When QALY data were in a distribution with a left-skewed tail bounded by 0.5 QALYs (maximum QALYs accrued for a 6-month period), decrements of QALYs were predicted in the GLM regression with a gamma and log-link. The method of predicting decrements of QALYs was applied in a previous NIHR HTA report, 92 with decrements calculated as the difference between the maximum QALYs that could possibly be accrued within the time horizon of the analysis and the actual QALYs gained. This ensures that the QALY variable is right-skewed and left-bounded by 0, fitting into a gamma distribution.…”
Section: Discussionmentioning
confidence: 99%